KTP Laser assisted microendoscopic cricopharyngeal myotomy and web excision for dysphagia management - Hazarika, P. (Springer India, 2005)
Cricopharyngeal dysfunction is defined as the delayed or incomplete relaxation of the cricopharyngeal muscle during swallowing. This may cause dysphagia and aspiration, affecting the quality of life. For this condition, injection of botulinum toxin into the cricopharyngeus, dilatation of cricopharynx with bougies and external cricopharyngeal myotomy have been the treatment of choice with varying results. We present in this paper the treatment of this clinical condition by KTP 532 laser a recent advance in the field of Otolaryngology and Head and Neck Surgery. Very few series have been reported in literature so far regarding the use of laser for cricopharyngeal myotomy. This is perhaps the first series of eight cases of KTP laser assisted microendoscopic cricopharyngeal myotomy and web excision reporting the benefit of this treatment by an Indian author in an Indian Journal. KTP laser assisted cricopharyngeal myotomy avoids an external scar; aids precise incision at the cricopharynx by direct visualization, brings optimum results in deglutition and reduces postoperative morbidity and complications. The short hospital stay reduces the overall cost. The use of KTP 532 laser in the treatment of selected cases with cricopharyngeal dysfunction is therefore safe and effective.